ANALISIS KELAYAKAN USAHA ATAP RUMBIA DI KECAMATAN BENGKALIS KABUPATEN BENGKALIS - Muhammad, Dzakwan Ayuti Naufal; Rita, Iyan Yani; Hilmah, Zuryani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to analyze the thatch roof business from the aspects of marketing, finance, and Break Event Point. Sampling using purposive sampling method of 20 respondents, data analysis used Net Present Value, Benefit Cost Ratio, Internal Rate Of Return. The analysis results show that from the financial aspect it is feasible, seen from the value of the Net Present Value, Net Benefit Cost Ratio, and the value of its Internal Rate of Return. The results of this study indicate that the thatch roof business is quite good, this can be seen from the increase in the number of requests every year. The feasibility of thatch roof business in Bengkalis District is seen from the financial aspect that this business is feasible, because the NPV value is> 0. Net B / C Ratio value is more than 1. The business has favorable prospects. The IRR value of 83.97% is greater than the interest rate of 20%, meaning that this business is feasible. The thatched roof business in Bengkalis District has succeeded in selling products above the break even point value. The results of the break even point analysis show that the minimum sales amount is 15.65 m2 with a minimum sales value of Rp. 367,297,297, -.Keywords: Marketing Aspects, Financial Aspects, Break-even Point